1995
DOI: 10.1093/brain/118.6.1497
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral glucose metabolism in children with deterioration of one or more cognitive functions and continuous spike-and-wave discharges during sleep

Abstract: The Landau-Kleffner syndrome (LKS) and the syndrome of continuous spike-and-wave discharges during slow sleep (CSWS) were originally described, and are still considered, separately. The former combines an acquired aphasia with spike-and-wave discharges that are activated by slow wave sleep, behavioural disturbances, and sometimes epileptic seizures. The latter is characterized by continuous spike-and-wave discharges during slow wave sleep, usually combined with global intellectual deterioration and epileptic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
94
1
8

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 0 publications
8
94
1
8
Order By: Relevance
“…Hypometabolic areas in FIRES are also consistent with neuropsychologic findings, as previously reported in other epilepsy conditions: low cognitive functioning with the extent and bilaterality of frontal hypometabolism (36), language disorders with external temporal involvement and, particularly, receptive troubles with posterior parietotemporal hypometabolism (37), behavior disorders with orbitofrontal hypometabolism, and major sociocognitive troubles with bilateral hypometabolism of the superior temporal gyrus (according to PET findings in autistic children (38)). A quite similar network has been identified in children with aggressive behavior (39).…”
Section: Temporal-orbitofrontal Dysfunction In Fires: From Areas To Nsupporting
confidence: 89%
“…Hypometabolic areas in FIRES are also consistent with neuropsychologic findings, as previously reported in other epilepsy conditions: low cognitive functioning with the extent and bilaterality of frontal hypometabolism (36), language disorders with external temporal involvement and, particularly, receptive troubles with posterior parietotemporal hypometabolism (37), behavior disorders with orbitofrontal hypometabolism, and major sociocognitive troubles with bilateral hypometabolism of the superior temporal gyrus (according to PET findings in autistic children (38)). A quite similar network has been identified in children with aggressive behavior (39).…”
Section: Temporal-orbitofrontal Dysfunction In Fires: From Areas To Nsupporting
confidence: 89%
“…A large majority of authors agree on the fact that the main EEG characteristic in LKS is consituted by highamplitude spike-waves, organized in various foci, with a predominence over temporal and parieto-occipital areas (Beaumanoir, 1992;Maquet et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The waking EEG shows focal, multifocal or bilateral spike-wave discharges, the topography of which fluctuates with time (Maquet et al, 1995). These spike-wave discharges increase during slow-wave sleep and may become continuous.…”
mentioning
confidence: 99%
“…There are also reports of bizarre behavior (Kyllerman et al, 1996;Morikawa et al, 1995), emotional lability, anxiety and phobia (Morikawa et al, 1995), and of autistic-like behavior (Bulteau et al, 1995;Kyllerman et al, 1996), although a case of CSWS with autistic regression is a rare occurrence: McVicar et al (2005) conducted a retrospective review of children with language regression studied at their Institute for more than 12 years, finding that only 10 children had ESES, only one of whom had a history of autism and language regression. Some works report a deterioration of language with a tendency toward expressive aphasia with lexical and syntactic difficulties, and a generally preserved comprehension (Debiais et al, 2007;MacAllister & Schaffer, 2007), learning difficulties at school, poor reasoning and short-term memory deficits (De Negri et al, 1997;Tassinari et al, 1992;, and also motor impairments, such as ataxia, dystonia and dyspraxia (Maquet et al, 1995;Tassinari et al, 2000). Roulet-Perez et al (1993) reported clinical manifestations suggestive of a poor functioning in skills correlated to executive functions.…”
Section: Neuropsychological and Behavioral Profilementioning
confidence: 99%